OCULAR ALIGNMENT AFTER BILATERAL RECTUS MUSCLE RECESSION FOR INTERMITTENT EXOTROPIA - Mokhtar, Nur Hafiza; Mustapa , Khatijah; Chew, Fiona LM (International Journal of Allied Health Sciences, 2021)
Background: Intermittent exotropia (IXT) is a common type of strabismus where there is an intermittent outward deviation of the eyes. Aim of this study is to assess post-surgical ocular alignment and to evaluate changes in the deviation angle over a 12- months period in patients who underwent surgical intervention for IXT. Methodology: Retrospective cohort study of patients who underwent bilateral lateral rectus recession performed by a single surgeon in 2018. Demographic details, pre- and post-surgical exotropic angle measurements were recorded. Patients were assigned based on their motor success. A post-surgical ocular deviation angle of orthophoria, exo-deviation or eso-deviation of less than 10 prism diopters (PD) was classified as success while the remaining subjects were assigned to the failure group. Results: A total of 41 subjects, aged between 2 to 67 years old (mean age of 14.4 years, SD 15.65) were recruited. There were 46.3% females and 53.7% males. Majority subjects were Malay (73.2%), Chinese (26.8%). Motor success was achieved in 29 (75.6%), recurrence in 22.0% and overcorrection in 2.4% subjects. There was a good correlation between ocular alignment at 6- and 12-months post-surgery (?= 0.53, P <0.05). There was no significant difference in the mean deviation magnitude over a 12-months period post-surgery (F (1.266, 50.631)= 0.227, P<0.001). Conclusion: The good success rate and stability in the ocular alignment suggests strabismus surgery as a good treatment for intermittent exotropia patients. Keywords: intermittent exotropia, surgery, strabismus